Survival in patients with metastatic recurrent breast cancer after adjuvant chemotherapy. Issue 6 (12th October 2012) - Tevaarwerk, Amye J.; Gray, Robert J.; Schneider, Bryan P.; Smith, Mary Lou; Wagner, Lynne I.; Fetting, John H.; Davidson, Nancy; Goldstein, Lori J.; Miller, Kathy D.; Sparano, Joseph A.
Abstract BACKGROUND: Population‐based studies have shown improved survival for patients diagnosed with metastatic breast cancer over time, presumably because of the availability of new and more effective therapies. The objective of the current study was to determine whether survival improved for patients who developed distant recurrence of breast cancer after receiving adjuvant therapy. METHODS: Adjuvant chemotherapy trials coordinated by the Eastern Cooperative Oncology Group that accrued patients between 1978 and 2002 were reviewed. Survival after distant disease recurrence was estimated for progressive time periods, and adjusted for baseline covariates in a Cox proportional hazards model. RESULTS: Of the 13, 785 patients who received adjuvant chemotherapy in 11 trials, 3447 (25%) developed distant disease recurrence; the median survival after recurrence was 20 months (95% confidence interval, 19 months‐21 months). Factors associated with inferior survival included a shorter distant recurrence‐free interval (DRFI), estrogen receptor‐negative and progesterone receptor‐negative disease, the number of positive axillary lymph nodes present at the time of diagnosis, and black race (P < .0001 for all). When the time period of recurrence was added to the model, it was not found to be significantly associated with survival for the general population with disease recurrence. Survival improved over time only in those patients with hormone receptor‐negative disease with a DRFI ≤ 3 years, both among the 5 most recent and the entire trial data sets (P = .01 and P = .05, respectively). CONCLUSIONS: In contrast to reports from population‐based studies, no general improvement in survival was observed over the last 30 years for patients who developed distant disease recurrence after adjuvant chemotherapy after adjusting for DRFI. Improved survival for patients with hormone receptor‐negative disease with a short DRFI suggests a benefit from trastuzumab. Cancer 2013. © 2012 American Cancer Society.